The Fluidity of the Fantastic: Todorov’s Legacy to Literary Criticism - Bolongaro, Eugenio (Ticontre. Teoria Testo Traduzione, 2014)
This article addresses the contemporary significance of Tzvetan Todorov’s seminal essay The Fantastic. A Structural Approach to a Literary Genre. The enduring contribution of Todorov’s essay to literary theory and criticism is examined in the first part of the discussion which focuses on three key mo- ments in the critic’s argument: the defense of genre as a crucial conceptual category for literary analysis, the concept of hesitation or wavering which is at the core of the definition of the fantastic genre, and the idea that there is strong link between the fantastic genre and the acceleration of plot. It is argued that each of these moments remains richly suggestive and productively engage contemporary preoccupations about the role of literary theory and the complex inter-relation between realist and non-realist fiction, as well as the ethical dimension of literary narratives. The second part of the essay approaches The Fantastic as a work of rather than merely about literature. From this perspective the essay emerges as the trace of a fascinating conceptual adventure. A careful rereading of Todorov’s work reveals the genesis, evolution and eventual disper- sion of the critic’s insights as they break out of the initial structuralist framework and open horizons that Todorov’s himself did not anticipate and can- not fully control. This excess of meaning is the surest evidence of Todorov’s outstanding achievement.